Pemasangan Plang Jalan sebagai Wujud Kolaborasi Mahasiswa dan Masyarakat dalam Pembangunan Desa Pantai Bahagia Kecamatan Muara Gembong Bekasi - Tanisri, Roberta Heni Anggit; Rizki, M Aliffathur; Rifqi, Muhamad; Wibowo, Andika Prastiyo; Faiz, Muhammad Hisyam; Dwianto, Aditia Fajar; Naufal, Iqbal; Sahid, Syaian Yanis; Aqilla, Raffary; Ikhsan, Ario Muhammad; Syafiq, Sulthon Muammar (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2025)
The improvement of village infrastructure facilities is an important part of supporting rural development related to mobility, navigation, and area recognition. Pantai Bahagia village, located in Muara Gembong sub-district og Bekasi regency, does not yet have directional signpostd as navigation for visitors to the village area. This community service activity aims to install directional signposts as am effort to improve accessibility and area identity in Pantai Bahagia village. The method used is a participatory approach through KKN involving students, village officials, and local residents. The results show that the presence of directinal signposts helps facilitate visitors and the community in navigation and strengthens the village’s image and spatial arrangement visually. For Pantai Bahagia village, it is essential to carry out the process of developing similar facilities sustainably and integrated within the village development plan.